Foundation characteristics of edible Musa triploids revealed from allelic distribution of SSR markers - Hippolyte, I.; Jenny, C.; Gardes, L.; Bakry, F.; Rivallan, R.; Pomies, V.; Cubry, Philippe; Tomekpe, Kodjo; Risterucci, A.M.; Roux, N.; Rouard, M.; Arnaud, Elizabeth; et al. (Oxford University Press, 2012)
The production of triploid banana and plantain (Musa spp.) cultivars with improved characteristics (e.g. greater disease resistance or higher yield), while still preserving the main features of current popular cultivars (e.g. taste and cooking quality), remains a major challenge for Musa breeders. In this regard, breeders require a sound knowledge of the lineage of the current sterile triploid cultivars, to select diploid parents that are able to transmit desirable traits, together with a breeding strategy ensuring final triploidization and sterility. Highly polymorphic single sequence repeats (SSRs) are valuable markers for investigating phylogenetic relationships.